Optimal soot blowing and repair plan for boiler based on HJB equation. (16th December 2022) - Wen, Jie; Shi, Yuanhao; Pang, Xiaoqiong; Jia, Jianfang
Abstract : The optimization of boiler soot blowing strategy and repair plan is investigated based on Hamilton–Jacobi–Bellman (HJB) equation in this paper. From the perspective of soot, we build a Markov process with three modes to describe the boiler running process. For the sake of applying HJB equation, a cost function is constructed according to the built Markov model, and HJB equation is derived by using optimality principle. The optimal soot blowing strategy and repair plan can be obtained by solving HJB equation. Particularly, the properties of value function, which are regarded as the optimality conditions, can ensure the existence and uniqueness of HJB equation solution. On this basis, Kushner method is used to overcome the difficulty of obtaining analytical solution of HJB equation. Moreover, numerical simulations are performed to verify the effectiveness of the proposed method and analyse the robustness of the obtained soot blowing strategy and repair plan when the system parameters vary.